PENGARUH JUMLAH OPSI SAHAM DAN HARGA EKSEKUSI PADA KINERJA PERUSAHAAN - Kameswari, Luh Putu Lisa Anastasia; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 9 No 2 (2014), 2014)
The purpose of this study was to determine the effect of the stock options and the exercise price on the firm performance. Firm performance is proxied by ROA and number of stock options is proxied by the proportion of stock options. This research was conducted on ESOP adopters company listed on the Stock Exchange the period 1999 to 2012. Amount samples obtained by 29 companies with 52 observations were obtained by using purposive sampling technique. The data analysis technique used is multiple linear regressions performed 2 times. The analysis showed that the number of stock options granted has no effect on the performance of companies in the grant year and the next one year, while the exercise price in effect on the performance of the company in the grant year and the next one year.
Keywords: stock options, exercise price, and company performance